Improved conductivity of indium-tin-oxide film through the introduction of intermediate layer. (September 2016) - Ng, S.W.; Yam, F.K.; Beh, K.P.; Tneh, S.S.; Hassan, Z.
Abstract: A thin intermediate layer (Ag, AuSn, In, Ni, Sn, SiO2 ) was individually deposited on glass substrates prior to the deposition of indium-tin-oxide (ITO) thin film by radio-frequency (RF) magnetron sputtering employing ITO target (composition ratio of In2 O3 :SnO2  = 9:1). The structural, optical and electrical properties were investigated to compare the ITO thin film with and without an intermediate layer. The preferential orientation of all ITO films was along (222) plane. Although all thin films were polycrystalline, the presence of intermediate layer promoted the overall crystallinity. The sheet resistance and resistivity of the ITO film were reduced from ∼68 Ω/□ to ∼29–45 Ω/□, and 16.2 × 10 −4  Ω cm up to 7.58 × 10 −4  Ω cm, respectively, by inserting a thin metal layer underneath the ITO film, and it is dependent on the degree of crystallization. The optical transmittance in the visible region varies from 40 to 88% for different samples. Based on the evaluation from Tauc plot, the optical band gap falls in the range of 4.02–4.12 eV. Physical film thickness was compared with that evaluated by optical measurement in the visible range and the physical thickness was found to be smaller. Similarly, the carrier concentration/scattering time from Hall effect measurement were also compared with that from optical measurement in the infrared region. Haacke's figure of merit (FOM) was employed to assess the quality of the ITO films, and the highest FOM is credited to ITO/In up to ∼8 × 10 −3  Ω −1 in the visible light region. Highlights: Metal layer promotes crystallinity and reduces sheet resistance and resistivity. Sheet resistance: ITO/Ni < ITO/In ≈ ITO/AuSn < ITO/Ag < ITO/Sn < ITO/SiO2  ≈ ITO. ITO/Ni possesses lowest sheet resistance but ITO/In offers highest transmittance. Indium can serve as alternative metal layer to improve ITO conductivity.